Cross-Axis Coupling Effects in Single-Axis Nuclear Magnetic Resonance Gyroscopes - Zhiguo Wang; Yi Zhang; Xiang Zhan; Qiyuan Jiang; Hui Luo (Sensors, 2020)
Nuclear magnetic resonance gyroscopes (NMRGs) may be operated in an environment with violent vibration that usually contains both linear components and angular components. To analyze the influence of angular vibration on an NMRG, cross-axis coupling effects are studied. The cross-axis rotation rates induce an equivalent magnetic field. Its influence can be described by the Bloch equations. The approximate frequency shift and amplitude of the spin oscillator with an equivalent magnetic field in the cross-axis were obtained, which was validated by numerical simulation. The findings show that the angular vibration component leads to a remarkable error for the NMRG. When the angular vibration frequency is near the Larmor frequency, the oscillation frequency of the spins may be locked to the angular vibration frequency, destroying the NMRG’s ability to measure rotation rates. The cross-axis coupling problem should be considered in the design of an NMRG and corresponding inertial navigation systems.